Distribusi spasial mikroartropoda tanah berdasarkan jarak yang berbeda dari Pantai Utara Kota Semarang, Jawa Tengah - Anggi Aprilia Budi Prasetiani; Rully Rahadian; Mochamad Hadi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Soil microarthropods are soil mesofauna which has body size 0.02 - 0.17 mm. Distribution of soil fauna of an area depends on the condition of environment and the characteristic of biologic. The objective of this research is to determine the distribution of spatial and structure community of soil microarthropods in several locations that have different distance from the northern coast of Semarang City. The research was conducted at December 2017 until June 2018. Sampling was conducted at three different locations, that is area around of Tawang Station, the Undip Pleburan Campus area, and the Cemoro Songo Park area. Samples were extracted and identified at the Ecology and Biocytic Laboratory, and analysis of soil and C-organic material at the Soil Mechanics Laboratory and Environmental Laboratory. The results of identification found 53 species consist of 14 ordo and 11 families. The distribution of all microarthropods are almost included in clumped distributions. The abundance of microarthropods is dominated by Acari and Collembola. The evenness are included in the highest evenness categories with the highest location with a value of 0.93. The similarity of taxa are included in the lowest categories with a value of 10.26% -19.35%.